PENERAPAN MODEL PEMBELAJARAN PROBLEM BASEDLEARNING (PBL) UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA SEKOLAH DASAR - Maghpiri, Uni; Nurhamidah, Didah (Elementar : Jurnal Pendidikan Dasar, 2024)
Education is a conscious and planned effort to create a learning environment that supports students in developing their potential, whether spiritually, intellectually, or in skills, for the benefit of individuals, society, the nation, and the state. In modern learning, students play an active role as learning partners, while teachers act as facilitators and mediators. Islamic Religious Education (PAI) aims to guide students to understand, internalize, and practice Islamic teachings based on the Quran and Hadith for happiness in this world and the hereafter. However, PAI is often perceived as boring by students due to monotonous teaching methods such as lectures and assignments, which make students passive and less interested. This issue was identified during observations at SDN 005 Batu Aji, where students were afraid to ask questions, reluctant to solve problems in front of the class, and felt that the teacher's dominance was too strong. The proposed solution is the implementation of the Problem-Based Learning (PBL) model, which actively involves students in group discussions to solve problems, express opinions, and act as peer tutors. PBL is expected to improve student activity and learning outcomes, transforming their performance from below average to good or excellent